Coordinated firm-level work processes and macroeconomic resilience - Moritz Kuhn; Jinfeng Luo; Iourii Manovskii; Xincheng Qiu (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
The production processes at many firms rely on a highly choreographed and interdependent network of workers performing specialized jobs. We designed and implemented a targeted employer survey to measure the extent of coordination in work processes. We link this firm-level coordination measure to administrative data and find that firms with a more coordinated work process are more productive, pay higher wages, and experience lower worker turnover. Yet, these firms suffer more severe negative consequences from worker absences and adopt various strategies to mitigate such risk, the reliance on which we document. While the standard unemployment insurance policy pays benefits to workers who lose their jobs, the short-time work policy widely adopted in Germany compensates workers who remain employed with reduced hours for the associated loss of earnings. This policy can benefit employers with a more coordinated production process because they can lower the scale of production by reducing hours while keeping all workers needed for the production process employed, increasing the resilience of these employers to large idiosyncratic and aggregate shocks.
Keywords: E23; E24; J24; J65; 330; Labor markets; Coordination; Economic resilience; Work process; Covid-19